PENGEMBANGAN MODUL MATEMATIKA BERBASIS PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL KELAS VII SMP - Zainab Maudi Story; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2022)
This study was encouraged by students’ lack of interests in Mathematics, especially in linear equations and inequalities of one variable. Students consider the materials too difficult and hard to understand, which cause them to be passive during the lesson. This study aimed to develop a cooperative learning-based Mathematics teaching module with Numbered Head Together (NHT) type on linear equations and inequalities of one variable for grade VII of Junior High School in the academic year of 2018/2019. This study is classified as Research and Development type that involved students of SMP Muhammadiyah Ngemplak and SMP Negeri 2 Prambanan as the research subjects. This study collected both quantitative and qualitative data through interview and questionnaire. The data were analyzed using quantitative analysis, which then converted into qualitative analysis using Likert scale.This study discovered that: the average score from media expert judgment was 122 points with good criteria; the average score from the material expert judgment was 117 points with good criteria; and the average score from the students’ responses was 54.13 points with good criteria. Based on the research results, the cooperative learning-based Mathematics teaching module with Numbered Head Together (NHT) type on linear equations and inequalities of one variable for grade VII of Junior High School in the academic year of 2018/2019 is proper to use.